Detection of Bolt Looseness Based on Average Autocorrelation Function. (15th May 2021) - Wu, Jigang; Shao, Jun; Zhou, Gen; Yang, Deqiang; Cheng, Yuan
Abstract : Bolted connections are widely used in multiple engineering fields including aerospace and mechanical engineering due to their numerous advantages like the ability to bear relatively heavy loads, low costs, easy installation, and implementation. Bolt looseness may lead to costly disasters in industries and some cases of injuries. A new method for bolt looseness detection based on average autocorrelation function is proposed. It does not usually directly extract the looseness damage feature from the original response signal to detect the bolt looseness, but it uses the average autocorrelation function value at time lag T  = 0 of the vibration pixel displacement signal to establish the looseness damage index. In terms of structural arrangement of this paper, firstly, the theoretical background of the proposed method is given. Then, an experimental system for bolt looseness detection based on computer vision is designed, and a verification experiment is carried out with the bolted connection plate as the experimental object. The results show that the proposed method can effectively obtain the location of the looseness damage of the bolted connection plate, which provides a new technical reference for the online monitoring of the looseness damage of bolted connection plate.